Tinjauan yuridis pelaksanaan hak cipta dalam open access informasi - Sri Rumani (IJAL (Indonesian Journal of Academic Librarianship), 2017)
Copyright is an exclusive right (morally and economically) automatically owned by the creator, as a treasure of the minds of science, art, and literature. The development of science and technology affects the protection and legal certainty for the creator. This means that the creators and creators have competence, considering Indonesia has ratified the world copyright agreement with the Presidential Decree No.19 of 1997. Consequently there is an obligation to enact Law No.28 of 2014. In Indonesia, copyright issues originally arranged in Auteursweet 1912 (Undang invited the rights of authors 1912), called "author rights", as a legal product of the Dutch government. Indonesia in 1982 made the Act of Copyright No. 6 of 1982, which has been amended four times, the last Law No.28 of 2014. The methodology in this paper uses a literature study aimed at increasing the insight of librarians in the field of intellectual work produced by the creators. Therefore librarians must understand it, considering the task is related to copyright.